Behavioral Skills Training to Increase Appropriate Reactions of Adolescent Males in Residential Treatment. Issue 4 (July 2021) - Brogan, Kristen M.; Rapp, John T.; Edgemon, Anna Kate; Niedfeld, Amanda M.; Coon, Jodi C.; Thompson, Kelli R.; Burkhart, Barry R.
Adolescents in secured residential facilities may engage in excess behavior immediately following verbal directives or corrective statements from staff. Excess behavior may include verbal aggression, indices of disrespect (e.g., eye rolling, grunting, and obscene gestures), or even physical aggression. These excess behaviors may evoke further directives or corrective statements from staff that, in turn, escalate the adolescent's excess behavior and can produce undesirable effects for both the adolescent (e.g., loss of privileges) and staff members (e.g., increased burn out). Teaching detained adolescents to respond appropriately to staff directives and corrective statements may produce large collateral changes in the way staff interact with adolescents in detention facilities. These changes could be conceptualized as a behavioral cusp. We used behavioral skills training to teach 11 adolescent males to respond appropriately to staff directives. All 11 students showed low percentages of trials with appropriate reactions in baseline and high percentages of trials with appropriate reactions during treatment and generalization sessions. Further, two students showed maintenance of the skill 1 month and 5 months following treatment.